Correlation of Aspergillus flavus with the Concentration of Aflatoxin B1 in Ikan Kayu - Safika Safika (Jurnal Kedokteran Hewan, 2008)
The objective of this research was to know the contamination of Aspergillus flavus in ikan kayu and the number of aflatoxin B1 (AFB1) produced. Also the corelation the number of A. flavus with AFB1. Samples were taken from traditional markets in Banda Aceh and Lhokseumawe. The sample were used to isolation and identify A. flavus also detect the present of AFB1 by ELISA (Enzym Linked ImmunosorbantAssay). The result shows that all samples show the present of A. flavus with the concentration 1 x 102-61 x 102 Cfu/g and the concentration of AFB1 between 0.9-38.7 ppb. In conclusion the present A. flavus in ikan kayu has a corelation with the production of AFB1.